Preference of adult learners between the synchronous or asynchronous instructions in distance learning environment - Nailul Morad Mohd Nor; Mohamad Faisal Abd Karim (Proceedings of AICS - Social Sciences, 2013)
E-learning is expected to play a greater role in accommodating the needs of the adult learners to participate in the learning programs. Since most distance learners are adults, it is critical for educators to understand several aspects of adults such as how adults learn and their preferences in studying. These understanding could help educators to plan a more effective learning programs and to provide a better support services to help adult learners. This paper will attempt to highlight the preference of adult learners between the synchronous or asynchronous e-learning instruction. The discussion is based on a study conducted on adult learners who are studying at the School of Distance Education (SDE), Universiti Sains Malaysia in Malaysia. The synchronous instructions are the live video conferencing and video streaming which are held at certain scheduled time to augment the printing learning materials. The asynchronous e-learning instructions are in the form of recorded video conference and reading materials posted in the learning portal that are accessible to students at anytime and anywhere. Factors related to the usage of these e-learning instructions will be identified and discussed. Learners’ problems or avoidance in utilizing the e-learning instruction will also be noted.Keywords: E-learning, adult learners, synchronous instruction, asynchronous instruction